The effect of using the self examination method in learning some technical skills in volleyball - Thsyn, Mayada (Journal of Physical Education, 2010)
The research included five chapters, which included: -The first chapter includes the definition of the research, the introduction and the importance of the research. As for the problem, it is through the researcher’s acquaintance with the physical education lessons is the use of most of the teachers the method of presentation and explanation, which brought the factor of boredom to the students. Therefore, the researcher decided to use the self-examination method in order to achieve the principle of cooperation between the teacher and the student in the educational process. Research to identify the effect of using the self examination method on learning some technical skills in volleyball.As for the hypotheses, the first hypothesis was the existence of statistically significant differences between the pre and post tests of the experimental and control groups in favor of the post-tests, while the second hypothesis was the existence of statistically significant differences between the post tests between the experimental and control groups and in favor of the experimental group.And the human field, so it was students of the second stage / morning studies / Department of Physical Education / College of Basic Education / Al-Mustansiriya University, and the place was in the closed sports hall.The second semester includes theoretical studies and previous studies.The third chapter includes the research methodology and its field procedures, as the researcher used the experimental method to suit it to the nature of the research. To the validity and accuracy of the results, the researcher conducted homogeneity among the sample members according to the variables (age, height, weight). Chapter Four This chapter contains the presentation and analysis of test results and their discussion.Chapter Five This chapter contains the following conclusions:1- Both teaching methods used in research have an effect on skill learning.2- The learning ratios varied between the two methods in favor of the self-examination method.3- The self-examination method has proven effective in learning some technical skills in volleyball.As for the recommendations, they were: - 1- The necessity of adopting a self examination method in learning other technical skills in volleyball.2- Conducting similar studies on other samples of different ages, for both sexes, and for the rest of the offensive and defensive skills of volleyball.3- Conducting similar studies and research on other academic subjects.